2017
DOI: 10.1038/s41598-017-05550-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study on Association of Prostatic Calcifications with Clinical Symptoms and Results of Treatment in Men with type III prostatitis

Abstract: The purpose is to investigate the clinical significance of prostatic calculi in patients with chronic prostatitis and to discuss the possible treatment.The data from 277 young males with CP/CPPS were analyzed prospectively. Symptom severity was measured using the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) and the International Prostatic Symptoms Score (IPSS). Sexual function was assessed by the International Index of Erectile Function (IIEF-5) questionnaire. After four weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Patients suffered from CNP often feel genitourinary pain in the presence of uropathogenic bacteria or malignancy. Statistics revealed that the morbidity of CNP accounts for about 70%-90% of all prostatitis patients and with an increased ratio in recent years [1,2]. To date, much research has reported that the non-coding RNAs (ncRNAs), proteins might affect the development of CNP, while the potential mechanism was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients suffered from CNP often feel genitourinary pain in the presence of uropathogenic bacteria or malignancy. Statistics revealed that the morbidity of CNP accounts for about 70%-90% of all prostatitis patients and with an increased ratio in recent years [1,2]. To date, much research has reported that the non-coding RNAs (ncRNAs), proteins might affect the development of CNP, while the potential mechanism was still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…TA B L E 3 Correlation between subgroups of Age, BMI, Height, FBG and prostate volume TG, VLDL-C, FBG, TPSA and fPSA were significantly different between the mild and severe enlarged prostate patient groups. Kidney stones and prostate calculi were reported to be affected by an enlarged prostate,[29][30][31] whereas Fei et al32 reported that the PV was not different in choric prostatitis patients with or without prostate calculi. In our study, we found that PV did not impact the incidence of kidney stones, whereas prostate calculi were positively associated with the prevalence of severely enlarged prostates.…”
mentioning
confidence: 99%
“…It is speculated that it may be related to chronic inflammation of the prostate caused by tissue calcification, arteriosclerosis, and the imbalance of sex hormones in the prostate. Prostate calcification affected the symptoms and efficacy of CP [ 21 ], interacted with prostate inflammation [ 22 ], and was related to age and PV [ 23 ]. Hypertension is not only a risk factor for arteriosclerosis and calcification [ 24 ] but also a factor affecting PV [ 25 ].…”
Section: Discussionmentioning
confidence: 99%